Deleting and sorting files is beneficial – But only when you fully let go - Kyra Göbel; Cornelia Niessen (Computers in Human Behavior Reports)
Being surrounded by and having to work with large numbers of data files is a challenge many employees are facing in the increasingly complex world of work. The systematic organization of the work environment – that is, regularly sorting and deleting data files – is important to prevent distractions and enable focused work. However, following the concept of distributed cognition, related thoughts and insecurities also need to be addressed. Using a combination of controlled laboratory research (Think/No-Think paradigm) and an experience sampling approach (NLevel1 = 1,476, NLevel2 = 158), the present study examined effects of the interplay between sorting/deleting files and the ability to control thoughts on mental effort, task focus, and work performance. Multilevel modeling results revealed several cross-level interactions: For people with lower thought control ability, deleting files resulted in higher mental effort and lower task performance. Sorting files led to higher task focus and work performance, but only for people with higher thought control ability. Overall, sorting and deleting seem to be beneficial when people are also able to successfully control thoughts. These findings underscore the importance of considering both external and internal factors in workplace organization, advocating for multifaceted interventions to support individuals in cluttered work environments.